Independent schools of the United Kingdom. ([Londonn] E.J. Burrows, 1997)
Annual
Annual.
Keywords: Public schools, Endowed (Great Britain) -- Directories; Private schools -- Great Britain -- Directories; Private schools -- Ireland -- Directories